Waste Recycling Processing in Indonesian Tourist Attractions: Problems and Challenges of Implementing Legal Policies Restricting Plastic Use - I Wayan Koko Suryawan; Sapta Suhardono; Mega Mutiara Sari; Iva Yenis Septiariva (School of Postgraduate Studies, Diponegoro Univer, 2024)
Efficient waste management remains a pivotal challenge at Indonesian tourist sites. This study conducts a literature review to dissect the prevalent issues and necessary policy interventions in recycling waste within these locales. Results reveal that current policies on plastic usage are inadequately enforced, largely due to insufficient awareness and stakeholder engagement. Key barriers include a lack of infrastructure, minimal community participation in recycling initiatives, and limited regulatory oversight. To address these issues, the study suggests amplified enforcement of existing plastic regulations, enhancement of waste management infrastructure, and a boost in community involvement. The study advocates for a cohesive approach involving government authorities, tourism businesses, waste management entities, and local communities to heighten accountability and environmental stewardship. It is posited that with collective effort, waste management in Indonesian tourist spots can be significantly improved, thus yielding environmental and social dividends.